Rebalancing Growth in Asia : Economic Dimensions for China - Arora, Vivek; Cardarelli, Roberto (Washington, D.C. : International Monetary Fund, 2013)
This is a Chinese translation of "Rebalancing Growth in Asia: Economic Dimensions for China.".
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet